Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Let's analyze each of the given equations to determine which ones have exactly one solution.
### Equation (A)
[tex]\[ 12x + 12 = 13x - 12 \][/tex]
First, we'll isolate [tex]\(x\)[/tex] by moving all terms involving [tex]\(x\)[/tex] to one side and the constant terms to the other side:
[tex]\[ 12x + 12 = 13x - 12 \][/tex]
Subtract [tex]\(12x\)[/tex] from both sides:
[tex]\[ 12 = x - 12 \][/tex]
Add 12 to both sides:
[tex]\[ 24 = x \][/tex]
Therefore, equation (A) has exactly one solution, [tex]\(x = 24\)[/tex].
### Equation (B)
[tex]\[ -13x + 12 = 13x + 13 \][/tex]
Again, we'll isolate [tex]\(x\)[/tex] by moving all terms involving [tex]\(x\)[/tex] to one side and the constant terms to the other side:
[tex]\[ -13x + 12 = 13x + 13 \][/tex]
Add [tex]\(13x\)[/tex] to both sides:
[tex]\[ 12 = 26x + 13 \][/tex]
Subtract 13 from both sides:
[tex]\[ -1 = 26x \][/tex]
Divide both sides by 26:
[tex]\[ x = -\frac{1}{26} \][/tex]
Therefore, equation (B) has exactly one solution, [tex]\(x = -\frac{1}{26}\)[/tex].
### Equation (C)
[tex]\[ -13x + 12 = 13x - 13 \][/tex]
Isolating [tex]\(x\)[/tex], move all terms involving [tex]\(x\)[/tex] to one side and the constants to the other side:
[tex]\[ -13x + 12 = 13x - 13 \][/tex]
Add [tex]\(13x\)[/tex] to both sides:
[tex]\[ 12 = 26x - 13 \][/tex]
Add 13 to both sides:
[tex]\[ 25 = 26x \][/tex]
Divide both sides by 26:
[tex]\[ x = \frac{25}{26} \][/tex]
Therefore, equation (C) has exactly one solution, [tex]\(x = \frac{25}{26}\)[/tex].
### Equation (D)
[tex]\[ 12x + 12 = 13x + 12 \][/tex]
Isolating [tex]\(x\)[/tex], move all terms involving [tex]\(x\)[/tex] to one side and the constants to the other side:
[tex]\[ 12x + 12 = 13x + 12 \][/tex]
Subtract [tex]\(12x\)[/tex] from both sides:
[tex]\[ 12 = x + 12 \][/tex]
Subtract 12 from both sides:
[tex]\[ 0 = x \][/tex]
Therefore, equation (D) has exactly one solution, [tex]\(x = 0\)[/tex].
### Conclusion
Upon reviewing the calculations, it is evident that each of the equations (A), (B), (C), and (D) has exactly one solution.
So, the correct answer is:
- (A)
- (B)
- (C)
- (D)
### Equation (A)
[tex]\[ 12x + 12 = 13x - 12 \][/tex]
First, we'll isolate [tex]\(x\)[/tex] by moving all terms involving [tex]\(x\)[/tex] to one side and the constant terms to the other side:
[tex]\[ 12x + 12 = 13x - 12 \][/tex]
Subtract [tex]\(12x\)[/tex] from both sides:
[tex]\[ 12 = x - 12 \][/tex]
Add 12 to both sides:
[tex]\[ 24 = x \][/tex]
Therefore, equation (A) has exactly one solution, [tex]\(x = 24\)[/tex].
### Equation (B)
[tex]\[ -13x + 12 = 13x + 13 \][/tex]
Again, we'll isolate [tex]\(x\)[/tex] by moving all terms involving [tex]\(x\)[/tex] to one side and the constant terms to the other side:
[tex]\[ -13x + 12 = 13x + 13 \][/tex]
Add [tex]\(13x\)[/tex] to both sides:
[tex]\[ 12 = 26x + 13 \][/tex]
Subtract 13 from both sides:
[tex]\[ -1 = 26x \][/tex]
Divide both sides by 26:
[tex]\[ x = -\frac{1}{26} \][/tex]
Therefore, equation (B) has exactly one solution, [tex]\(x = -\frac{1}{26}\)[/tex].
### Equation (C)
[tex]\[ -13x + 12 = 13x - 13 \][/tex]
Isolating [tex]\(x\)[/tex], move all terms involving [tex]\(x\)[/tex] to one side and the constants to the other side:
[tex]\[ -13x + 12 = 13x - 13 \][/tex]
Add [tex]\(13x\)[/tex] to both sides:
[tex]\[ 12 = 26x - 13 \][/tex]
Add 13 to both sides:
[tex]\[ 25 = 26x \][/tex]
Divide both sides by 26:
[tex]\[ x = \frac{25}{26} \][/tex]
Therefore, equation (C) has exactly one solution, [tex]\(x = \frac{25}{26}\)[/tex].
### Equation (D)
[tex]\[ 12x + 12 = 13x + 12 \][/tex]
Isolating [tex]\(x\)[/tex], move all terms involving [tex]\(x\)[/tex] to one side and the constants to the other side:
[tex]\[ 12x + 12 = 13x + 12 \][/tex]
Subtract [tex]\(12x\)[/tex] from both sides:
[tex]\[ 12 = x + 12 \][/tex]
Subtract 12 from both sides:
[tex]\[ 0 = x \][/tex]
Therefore, equation (D) has exactly one solution, [tex]\(x = 0\)[/tex].
### Conclusion
Upon reviewing the calculations, it is evident that each of the equations (A), (B), (C), and (D) has exactly one solution.
So, the correct answer is:
- (A)
- (B)
- (C)
- (D)
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.